Environment-friendly degradable heat insulation fiber and preparation method thereof
By combining modified activated carbon with polylactic acid resin, environmentally friendly degradable thermal insulation fibers are prepared, which solves the problem that polylactic acid fiber is difficult to eliminate odor and odor removal, achieves high fracture strength and good odor removal effects, and expands the scope of application.
Patent Information
- Application Number
- CN202411885817.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing polylactic fibers are difficult to effectively eliminate odors and remove odors, which limits its application scope.
Modified activated carbon is used as raw material, and activated carbon is treated by tetrabutyl titanate, 3-allyloxypithyltrimethoxysilica, diethylaminoethyl methacrylate, trifluoroethyl acrylate and other substances to increase its ability to deodorize and remove odors, and combined with polylactic acid resin, bio-based thermal insulation fillers, etc., to prepare environmentally friendly degradable thermal insulation fibers.
The breaking strength and odor removal effect of environmentally friendly degradable thermal insulation fibers are improved, and the odor removal rate of ammonia gas is >56% and the odor removal rate of acetic acid is >51%, which expands its application range and meets market demand.
Smart Images

Figure BDA0005199258700000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polylactic acid fibers, and more specifically, to an environmentally friendly degradable thermal insulation fiber and a preparation method thereof. Background Art
[0002] With the enhancement of environmental awareness, traditional thermal insulation materials are mainly inorganic materials such as ceramic fibers and aluminum silicate fibers, and the environmental problems caused by their difficulty in degradation are becoming increasingly prominent. As a new type of environmentally friendly material, environmentally friendly degradable thermal insulation fibers have received extensive attention and attention from many researchers, and have been applied to various fields such as textiles, packaging, and aerogels. In the prior art, environmentally friendly degradable thermal insulation fibers often use polylactic acid fibers, which have certain degradability and can meet environmental protection requirements. However, polylactic acid fibers are difficult to effectively deodorize and remove odors, which limits the scope of application. Summary of the invention
[0003] In order to improve the deodorizing and odor-removing effects of environmentally friendly degradable thermal insulation fibers, the present application provides an environmentally friendly degradable thermal insulation fiber and a preparation method thereof.
[0004] In the first aspect, the present application provides an environmentally friendly degradable thermal insulation fiber, which adopts the following technical solution: An environmentally friendly degradable thermal insulation fiber is mainly made of the following raw materials in parts by weight: 70-90 parts of polylactic acid resin, 10-25 parts of bio-based thermal insulation filler, 3-8 parts of a compatibilizer, 10-15 parts of modified activated carbon, 0.1-0.5 parts of a silane coupling agent, and 0.5-1.5 parts of other additives; the modified activated carbon is obtained by treating activated carbon with tetrabutyl titanate, 3-allyloxypropyl trimethoxysilane, diethylaminoethyl methacrylate, and trifluoroethyl acrylate.
[0005] The environmentally friendly degradable thermal insulation fiber of the present application uses polylactic acid resin as the main material. Polylactic acid resin has good environmental protection and degradability. On this basis, bio-based thermal insulation fillers are added, which have excellent thermal insulation and heat preservation properties, and are also degradable, so that the environmentally friendly degradable thermal insulation fiber has good degradability and thermal insulation properties.
[0006] Modified activated carbon is added to the raw materials of environmentally friendly degradable thermal insulation fiber, titanium dioxide is deposited on the surface of activated carbon, and the mutual cooperation between titanium dioxide and activated carbon is utilized to improve the deodorization and odor removal effect. 3-allyloxypropyl trimethoxysilane, diethylaminoethyl methacrylate, and trifluoroethyl acrylate are further grafted, and active groups such as amine, fluorine, ester, and ethyl are introduced to increase the types and number of groups, enhance the compatibility between modified activated carbon and raw materials, and the interface bonding ability, and improve the mechanical properties of environmentally friendly degradable thermal insulation fiber. The breaking strength of environmentally friendly degradable thermal insulation fiber is ≥7.0cN / dtex, the ammonia deodorization rate is >56%, and the acetic acid deodorization rate is >51%, showing the advantages of high breaking strength and good deodorization and odor removal effect, expanding the scope of application and meeting market demand.
[0007] Optionally, the modified activated carbon is prepared by the following method: S1, mixing ethanol and tetrabutyl titanate to obtain a tetrabutyl titanate ethanol solution; S2, mixing water and activated carbon, adding tetrabutyl titanate ethanol solution, stirring for 30-60 minutes, filtering, and obtaining titanium dioxide modified activated carbon; S3. Mix water and emulsifier, add titanium dioxide modified activated carbon, and then add 3-allyloxypropyltrimethoxysilane, stir for 30-60 minutes, then add diethylaminoethyl methacrylate, trifluoroethyl acrylate, and initiator, stir for 1-3 hours, filter, wash, and dry to obtain modified activated carbon.
[0008] Optionally, the weight ratio of the activated carbon, tetrabutyl titanate, 3-allyloxypropyltrimethoxysilane, diethylaminoethyl methacrylate, trifluoroethyl acrylate and initiator is 100:(9-11):(4-6):(2-4):(2-4):(0.1-0.3).
[0009] By adopting the above technical solution, tetrabutyl titanate forms titanium dioxide when it meets water, and titanium dioxide is deposited on the surface of activated carbon. Then, the siloxy group in 3-allyloxypropyltrimethoxysilane is used to achieve grafting, and then the polymerization reaction of carbon-carbon double bonds is used to achieve the grafting of diethylaminoethyl methacrylate and trifluoroethyl acrylate. The modified activated carbon preparation method of the present application is carried out in steps of deposition, grafting, and polymerization, which not only facilitates the preparation of modified activated carbon, but also ensures the quality of modified activated carbon, and enhances the breaking strength and deodorization rate of environmentally friendly degradable thermal insulation fiber.
[0010] Optionally, in the method for preparing modified activated carbon, in step S1, the weight ratio of tetrabutyl titanate and ethanol is (9-11):(80-120).
[0011] Optionally, in the modified activated carbon preparation method, in step S2, the weight ratio of activated carbon to water is 1:(8-12).
[0012] Optionally, in the modified activated carbon preparation method, in step S3, the weight ratio of 3-allyloxypropyltrimethoxysilane, water, and emulsifier is (4-6):(800-1200):(5-10).
[0013] Optionally, the initiator is one or more of ammonium persulfate, sodium persulfate, and potassium persulfate.
[0014] By adopting the above technical solution, the initiator is limited, which facilitates the selection of the initiator. Moreover, ammonium persulfate, sodium persulfate and potassium persulfate are abundant and easy to obtain.
[0015] Optionally, the emulsifier is one or more of sodium stearate, sodium lauryl sulfate, Tween 40, Tween 80, Span 40, and Span 80.
[0016] In many embodiments, the emulsifier is Tween 80. The emulsifier may also be selected as sodium stearate, sodium lauryl sulfate, Tween 40, Span 40, Span 80 as needed, but is not limited to the listed options. Other options not listed within the selection range are also applicable.
[0017] Optionally, the activated carbon is one or more of coconut shell activated carbon, bamboo charcoal activated carbon, and coal-based activated carbon.
[0018] Optionally, the average particle size of the activated carbon is 50-500 nm. Preferably, the average particle size of the activated carbon is 50-300 nm. More preferably, the average particle size of the activated carbon is 50-200 nm.
[0019] Optionally, the silane coupling agent is one or more of methacryloxytrimethylsilane, 3-allyloxypropyltrimethoxysilane, and 3-aminopropyltriethoxysilane.
[0020] By adopting the above technical scheme, the silane coupling agent is limited, which facilitates the selection of the silane coupling agent. It can also enhance the compatibility between the raw materials, improve the internal interface bonding force of the environmentally friendly degradable thermal insulation fiber, and enhance the mechanical properties and heat resistance stability of the environmentally friendly degradable thermal insulation fiber.
[0021] Optionally, at 190° C. and 2.16 kg, the melt mass flow rate of the polylactic acid resin is 30-200 g / 10 min. Preferably, at 190° C. and 2.16 kg, the melt mass flow rate of the polylactic acid resin is 50-100 g / 10 min.
[0022] By adopting the above technical solution, the melt mass flow rate of the polylactic acid resin is limited, thereby ensuring a stable source of the polylactic acid resin and facilitating the processing and molding of the environmentally friendly degradable thermal insulation fiber.
[0023] Optionally, the bio-based thermal insulation filler is one or both of plant fiber and animal fiber.
[0024] By adopting the above technical solution, the bio-based thermal insulation filler is optimized, which not only facilitates the selection of bio-based thermal insulation fillers, but also plant fibers and animal fibers have good thermal insulation, heat preservation, sound absorption, and degradability, which can meet environmental protection requirements.
[0025] Optionally, the plant fiber is one or more of hemp fiber, flax fiber, and cotton fiber.
[0026] Optionally, the animal fiber is one or more of wool, cashmere, and silk.
[0027] Optionally, the plant fibers have an average length of 1-5 mm and an average diameter of 10-20 μm.
[0028] Optionally, the compatibilizer is one or more of ethylene-acrylate-glycidyl methacrylate copolymer, maleic anhydride grafted polypropylene, maleic anhydride grafted polyethylene, and butylene terephthalate.
[0029] By adopting the above technical scheme, the compatibilizer is optimized, which facilitates the selection of the compatibilizer. It can also increase the compatibility between the raw materials, enhance the integrity of the environmentally friendly degradable thermal insulation fiber, and ensure the quality of the environmentally friendly degradable thermal insulation fiber.
[0030] Optionally, the other auxiliary agents are one or more of antioxidants, light stabilizers, lubricants, and mildew inhibitors.
[0031] By adopting the above technical solution, other additives are limited, which makes it easy to select according to needs, thereby ensuring the quality of the environmentally friendly degradable thermal insulation fiber.
[0032] Optionally, the other auxiliary agent is an antioxidant. Preferably, the antioxidants are antioxidant 1010 and antioxidant 168, and the weight ratio of antioxidant 1010 to antioxidant 168 is (1-3): (1-3).
[0033] In multiple embodiments, the weight ratio of antioxidant 1010 and antioxidant 168 is 1:1, and the weight ratio can also be set to 1:2, 1:3, 2:1, 2:3, 3:1, 3:2 as needed, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] In a second aspect, the present application provides a method for preparing the environmentally friendly degradable thermal insulation fiber, which adopts the following technical solution: A method for preparing the environmentally friendly degradable thermal insulation fiber comprises the following steps: T1. Mixing polylactic acid resin, bio-based thermal insulation filler, compatibilizer, modified activated carbon, silane coupling agent, and other additives to obtain a mixture; T2, heating and melting the mixture, extruding and granulating, and obtaining polylactic acid masterbatch; T3, heating and melting the polylactic acid masterbatch, spraying and spinning, and obtaining the fiber body; T4. Heat-treating the fiber body for 5-15 minutes at a temperature of 90-110° C. and a draft of 3-8%, and cooling the fiber body to room temperature to obtain an environmentally friendly degradable thermal insulation fiber.
[0035] By adopting the above technical solution, the mixed materials are first mixed and processed into polylactic acid masterbatch. Then, the fiber body is obtained by jet spinning. After that, the fiber body is heat-treated to improve the internal structure of the fiber body, orient the fiber in the stress direction, and enhance the structural stability of the fiber body. The preparation method of the present application ensures that the raw materials are fully mixed through the mutual coordination between the various steps, improves the deformation resistance of the environmentally friendly degradable thermal insulation fiber, and improves the mechanical properties.
[0036] Optionally, in step T2, the melting temperature is 170-190° C. In many embodiments, the melting temperature is 180° C., and the melting temperature can also be set to 170° C., 175° C., 185° C., 190° C. as required, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0037] Optionally, in step T3, the melting temperature is 190-210° C. In many embodiments, the melting temperature is 200° C., and the melting temperature can also be set to 190° C., 195° C., 205° C., 210° C. as required, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0038] By adopting the above technical solution, the melting temperature in step T2 and step T3 is limited, which facilitates the preparation of polylactic acid masterbatch and fiber body.
[0039] An environmentally friendly degradable thermal insulation aerogel is made by using the environmentally friendly degradable thermal insulation fiber.
[0040] A method for preparing an environmentally friendly degradable thermal insulation aerogel comprises the following steps: E1. Mixing a solvent and an environmentally friendly degradable thermal insulation fiber, adding an auxiliary agent solution and mixing, to obtain a fiber dispersion; E2. Pour the fiber dispersion into a directional mold, directionally freeze, and freeze-dry to obtain an environmentally friendly, degradable, thermally insulating aerogel.
[0041] In summary, this application has at least the following beneficial effects: 1. The environmentally friendly degradable heat-insulating fiber of the present application, through the mutual cooperation between the raw materials, not only has good degradability and heat insulation, but also has the advantages of high breaking strength and good deodorization and odor removal effect. The breaking strength of the environmentally friendly degradable heat-insulating fiber is ≥7.0cN / dtex, the ammonia deodorization rate is >56%, and the acetic acid deodorization rate is >51%, which expands the scope of application and meets market demand.
[0042] 2. In the modified activated carbon preparation method of the present application, tetrabutyl titanate is used to form titanium dioxide modified activated carbon when it meets water, and then 3-allyloxypropyl trimethoxysilane is grafted by siloxy group, and then diethylaminoethyl methacrylate and trifluoroethyl acrylate are grafted by polymerization reaction. The method is adopted to carry out deposition, grafting and polymerization in steps, which not only facilitates the preparation of modified activated carbon, but also ensures the quality of modified activated carbon, and enhances the breaking strength and deodorization rate of environmentally friendly degradable thermal insulation fiber. DETAILED DESCRIPTION
[0043] In order to make the present application easier to understand, the present application will be further described in detail below in conjunction with the examples, which are merely illustrative and are not intended to limit the scope of application of the present application. The raw materials or components used in the present application can be obtained through commercial routes or conventional methods unless otherwise specified.
[0044] Preparation Example Preparation Example 1 A modified activated carbon is prepared by the following method: S1. Add 10 g of tetrabutyl titanate to 100 g of ethanol, and stir for 3 min to obtain a tetrabutyl titanate ethanol solution.
[0045] S2. Add 100 g of activated carbon to 1000 g of water, stir for 10 min, add the tetrabutyl titanate ethanol solution obtained in step S1, stir for 50 min, and then filter to obtain titanium dioxide modified activated carbon.
[0046] Among them, the activated carbon is coconut shell activated carbon, and the average particle size of the coconut shell activated carbon is 80nm.
[0047] S3, add 8g of emulsifier to 1000g of water, and stir for 3min. Add the titanium dioxide modified activated carbon obtained in step S2, and stir for 10min. Then add 5g of 3-allyloxypropyl trimethoxysilane, and stir for 50min. Then add 3g of diethylaminoethyl methacrylate, 3g of trifluoroethyl acrylate, and 0.2g of initiator, and stir for 2h. Then filter, wash with water three times, and the amount of water used for each washing is 500g. Then dry to obtain modified activated carbon.
[0048] Among them, the emulsifier is Tween 80 and the initiator is ammonium persulfate.
[0049] Preparation Example 2 A modified activated carbon is prepared by the following method: S1. Add 9 g of tetrabutyl titanate to 80 g of ethanol, and stir for 3 min to obtain a tetrabutyl titanate ethanol solution.
[0050] S2, add 100g of activated carbon to 800g of water, stir for 10min, add the tetrabutyl titanate ethanol solution obtained in step S1, stir for 60min, and then filter to obtain titanium dioxide modified activated carbon.
[0051] Among them, the activated carbon is coconut shell activated carbon, and the average particle size of the coconut shell activated carbon is 80nm.
[0052] S3, add 5g of emulsifier to 800g of water, stir for 3min. Add the titanium dioxide modified activated carbon obtained in step S2, stir for 10min. Then add 6g of 3-allyloxypropyl trimethoxysilane, stir for 60min. Then add 4g of diethylaminoethyl methacrylate, 2g of trifluoroethyl acrylate, and 0.3g of initiator, stir for 3h. Then filter, wash with water three times, and use 500g of water for each washing. Then dry to obtain modified activated carbon.
[0053] Among them, the emulsifier is Tween 80 and the initiator is ammonium persulfate.
[0054] Preparation Example 3 A modified activated carbon is prepared by the following method: S1. Add 11 g of tetrabutyl titanate to 120 g of ethanol, and stir for 3 min to obtain a tetrabutyl titanate ethanol solution.
[0055] S2, add 100g of activated carbon to 1200g of water, stir for 10min, add the tetrabutyl titanate ethanol solution obtained in step S1, stir for 30min, and then filter to obtain titanium dioxide modified activated carbon.
[0056] Among them, the activated carbon is coconut shell activated carbon, and the average particle size of the coconut shell activated carbon is 80nm.
[0057] S3, add 10g of emulsifier to 1200g of water, stir for 3min. Add the titanium dioxide modified activated carbon obtained in step S2, stir for 10min. Then add 4g of 3-allyloxypropyl trimethoxysilane, stir for 30min. Then add 2g of diethylaminoethyl methacrylate, 4g of trifluoroethyl acrylate, 0.1g of initiator, stir for 1h. Then filter, wash with water three times, and use 500g of water for each wash. Then dry to obtain modified activated carbon.
[0058] Among them, the emulsifier is Tween 80 and the initiator is ammonium persulfate. Example
[0059] Table 1 Amount of each raw material of environmentally friendly degradable thermal insulation fiber (unit: × 10g) Example Example 1 Example 2 Example 3 Polylactic acid resin 80 70 90 Bio-based insulation fillers 15 25 10 Compatibilizer 5 8 3 Modified activated carbon 13 10 15 Silane coupling agent 0.3 0.5 0.1 Other additives 1 0.5 1.5 Example 1 An environmentally friendly degradable thermal insulation fiber, the raw materials and raw material ratios of which are shown in Table 1.
[0060] Among them, the polylactic acid resin is polylactic acid resin PLA-70. According to GB / T3682.1-2018 standard, at 190°C and 2.16kg, the melt mass flow rate of the polylactic acid resin is 70g / 10min; the bio-based thermal insulation filler is flax fiber, and the average length of the flax fiber is 2mm and the average diameter is 15μm; the compatibilizer is ethylene-acrylate-glycidyl methacrylate copolymer, and the ethylene-acrylate-glycidyl methacrylate copolymer is Arkema AX8900; the silane coupling agent is 3-aminopropyltriethoxysilane; the other auxiliary agent is an antioxidant, and the antioxidants are antioxidant 1010 and antioxidant 168, and the weight ratio of antioxidant 1010 to antioxidant 168 is 1:1; the modified activated carbon is prepared by the method of Preparation Example 1.
[0061] A method for preparing an environmentally friendly degradable thermal insulation fiber comprises the following steps: T1. Add bio-based thermal insulation filler, compatibilizer, modified activated carbon, silane coupling agent and other additives to polylactic acid resin, stir for 5 minutes, and obtain a mixture.
[0062] T2. Heat and melt the mixture at 180°C, extrude and granulate it to obtain polylactic acid masterbatch.
[0063] T3. Heat and melt the polylactic acid masterbatch at a temperature of 200°C, and spray and spin to obtain a fiber body.
[0064] T4. Heat-treat the fiber body at a temperature of 100° C. and a draft of 5% for 10 minutes, cool it to 23° C., and obtain an environmentally friendly degradable thermal insulation fiber.
[0065] Example 2 An environmentally friendly degradable thermal insulation fiber, which is different from Example 1 in that the raw material ratio of the environmentally friendly degradable thermal insulation fiber is different, and the raw material ratio is shown in Table 1.
[0066] Example 3 An environmentally friendly degradable thermal insulation fiber, which is different from Example 1 in that the raw material ratio of the environmentally friendly degradable thermal insulation fiber is different, and the raw material ratio is shown in Table 1.
[0067] Example 4 An environmentally friendly degradable thermal insulation fiber, which differs from Example 1 in that the source of the modified activated carbon in the raw materials of the environmentally friendly degradable thermal insulation fiber is different, and the modified activated carbon is prepared by the method of Preparation Example 2.
[0068] Example 5 An environmentally friendly degradable thermal insulation fiber, which differs from Example 1 in that the source of the modified activated carbon in the raw materials of the environmentally friendly degradable thermal insulation fiber is different, and the modified activated carbon is prepared by the method of Preparation Example 3.
[0069] Application Examples Application Example 1 An environmentally friendly degradable thermal insulation aerogel is prepared by the following method: E1. Add 20 g of environmentally friendly degradable heat-insulating fiber to 1000 g of solvent and stir for 30 min. Then add 100 g of auxiliary agent solution and stir for 2 h to obtain fiber dispersion.
[0070] Among them, the environmentally friendly degradable thermal insulation fiber is prepared by the method of Example 1; the solvent is a mixed solution of tert-butanol and water, and the weight ratio of tert-butanol to water is 7:3; the auxiliary agent solution is a mixed solution of adhesive, Tween 80, and solvent, and the weight ratio of adhesive, Tween 80, and solvent is 0.5:1:100, and the adhesive is 3-aminopropyltriethoxysilane.
[0071] E2. Pour the fiber dispersion into an oriented mold and freeze it for 3 hours at a temperature of -70°C. Then, freeze-dry it for 36 hours at a temperature of -40°C and a pressure of 5Pa to obtain an environmentally friendly degradable thermal insulation aerogel.
[0072] Application Example 2-5 An environmentally friendly degradable thermal insulation aerogel, which differs from Application Example 1 in that, in step E1, the sources of the environmentally friendly degradable thermal insulation fibers are different, and the environmentally friendly degradable thermal insulation fibers of Application Examples 2-5 are prepared respectively by the methods of Examples 2-5.
[0073] Comparative Example Comparative Example 1 An environmentally friendly degradable thermal insulation fiber, which differs from Example 1 in that an equal amount of activated carbon is used to replace modified activated carbon in the raw materials of the environmentally friendly degradable thermal insulation fiber.
[0074] Comparative Example 2 An environmentally friendly degradable thermal insulation fiber, which differs from Example 1 in that in the raw materials of the environmentally friendly degradable thermal insulation fiber, in the modified activated carbon preparation method, an equal amount of water is used to replace tetrabutyl titanate.
[0075] Comparative Example 3 An environmentally friendly degradable thermal insulation fiber, which differs from Example 1 in that in the raw materials of the environmentally friendly degradable thermal insulation fiber, in the modified activated carbon preparation method, an equal amount of 3-allyloxypropyltrimethoxysilane is used to replace diethylaminoethyl methacrylate and trifluoroethyl acrylate.
[0076] Comparative Example 4 An environmentally friendly degradable thermal insulation fiber, which differs from Example 1 in that in the raw materials of the environmentally friendly degradable thermal insulation fiber, in the modified activated carbon preparation method, an equal amount of diethylaminoethyl methacrylate is used to replace trifluoroethyl acrylate.
[0077] Comparative Example 5 An environmentally friendly degradable thermal insulation fiber, which differs from Example 1 in that in the raw materials of the environmentally friendly degradable thermal insulation fiber, in the modified activated carbon preparation method, an equal amount of trifluoroethyl acrylate is used to replace diethylaminoethyl methacrylate.
[0078] Performance Testing The environmentally friendly degradable thermal insulation fibers obtained in Examples 1-5 and Comparative Examples 1-5 were respectively taken as samples, and the following performance tests were performed on the samples. The test results are shown in Table 2.
[0079] Among them, the breaking strength of the sample is tested according to ISO5079-1995 "Determination of breaking strength and elongation of single fibers of textile fibers".
[0080] According to GB / T33610.2-2017 “Determination of deodorizing properties of textiles Part 2: Inspection tube method”, the deodorizing rate of the sample is tested.
[0081] Table 2 Test results As can be seen from Table 2, the environmentally friendly degradable thermal insulation fiber of the present application has a high breaking strength of 7.0-7.3 cN / dtex, and also has a high deodorization rate, with an ammonia deodorization rate of 56.5-59.8% and an acetic acid deodorization rate of 51.6-53.8%. Through the mutual coordination between the raw materials, the environmentally friendly degradable thermal insulation fiber not only has the effects of degradation and thermal insulation, but also has the advantages of high strength and good deodorization and odor removal effects, meeting market demand.
[0082] Comparing Example 1 with Comparative Example 1, activated carbon is added to the environmentally friendly degradable heat-insulating fiber of Comparative Example 1, while modified activated carbon is added to the environmentally friendly degradable heat-insulating fiber of Example 1. It can be seen that by modifying the activated carbon, the compatibility and mixing uniformity can be increased, and the breaking strength and deodorization rate can be improved.
[0083] Comparing Example 1 with Comparative Example 2, in the modified activated carbon of Comparative Example 2, the activated carbon was treated with organic matter; in the modified activated carbon of Example 1, the activated carbon was treated with organic matter and titanium dioxide. It can be seen that the mutual cooperation between titanium dioxide and activated carbon can significantly increase the ammonia deodorization rate and the acetic acid deodorization rate, so that the environmentally friendly degradable thermal insulation fiber exhibits a better deodorization and odor removal effect.
[0084] Comparing Example 1 with Comparative Examples 3-5, in the modified activated carbon of Comparative Example 3, 3-allyloxypropyl trimethoxysilicon was used to treat the titanium dioxide modified activated carbon; in the modified activated carbon of Comparative Example 4, 3-allyloxypropyl trimethoxysilicon and diethylaminoethyl methacrylate were used to treat the titanium dioxide modified activated carbon; in the modified activated carbon of Comparative Example 5, 3-allyloxypropyl trimethoxysilicon and trifluoroethyl acrylate were used to treat the titanium dioxide modified activated carbon; in the modified activated carbon of Example 1, 3-allyloxypropyl trimethoxysilicon, diethylaminoethyl methacrylate, and trifluoroethyl acrylate were used to treat the titanium dioxide modified activated carbon. It can be seen from this that on the basis of treating the titanium dioxide modified activated carbon with 3-allyloxypropyl trimethoxysilicon, further utilizing the mutual coordination between diethylaminoethyl methacrylate and trifluoroethyl acrylate can improve the interface bonding ability between the modified activated carbon and the raw material and enhance the fracture strength.
[0085] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application is described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the present invention may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same functions.
Claims
1. An environmentally friendly degradable thermal insulation fiber, characterized by: The invention is mainly made of the following raw materials in parts by weight: 70-90 parts of polylactic acid resin, 10-25 parts of bio-based thermal insulation filler, 3-8 parts of compatibilizer, 10-15 parts of modified activated carbon, 0.1-0.5 parts of silane coupling agent and 0.5-1.5 parts of other auxiliary agents; the modified activated carbon is obtained by treating activated carbon with tetrabutyl titanate, 3-allyloxypropyl trimethoxysilane, diethylaminoethyl methacrylate and trifluoroethyl acrylate.
2. The environmentally friendly degradable thermal insulation fiber according to claim 1, characterized in that: The modified activated carbon is prepared by the following method: S1, mixing ethanol and tetrabutyl titanate to obtain a tetrabutyl titanate ethanol solution; S2, mixing water and activated carbon, adding tetrabutyl titanate ethanol solution, stirring for 30-60 minutes, filtering, and obtaining titanium dioxide modified activated carbon; S3. Mix water and emulsifier, add titanium dioxide modified activated carbon, and then add 3-allyloxypropyltrimethoxysilane, stir for 30-60 minutes, then add diethylaminoethyl methacrylate, trifluoroethyl acrylate, and initiator, stir for 1-3 hours, filter, wash, and dry to obtain modified activated carbon.
3. The environmentally friendly degradable thermal insulation fiber according to claim 2, characterized in that: The weight ratio of the activated carbon, tetrabutyl titanate, 3-allyloxypropyl trimethoxysilane, diethylaminoethyl methacrylate, trifluoroethyl acrylate and initiator is 100:(9-11):(4-6):(2-4):(2-4):(0.1-0.3).
4. The environmentally friendly degradable thermal insulation fiber according to claim 2, characterized in that: The initiator is one or more of ammonium persulfate, sodium persulfate and potassium persulfate.
5. The environmentally friendly degradable thermal insulation fiber according to claim 1, characterized in that: The silane coupling agent is one or more of methacryloxytrimethylsilane, 3-allyloxypropyltrimethoxysilane and 3-aminopropyltriethoxysilane.
6. The environmentally friendly degradable thermal insulation fiber according to claim 1, characterized in that: At 190° C. and 2.16 kg, the melt mass flow rate of the polylactic acid resin is 30-200 g / 10 min.
7. The environmentally friendly degradable thermal insulation fiber according to claim 1, characterized in that: The bio-based thermal insulation filler is one or both of plant fiber and animal fiber.
8. The environmentally friendly degradable thermal insulation fiber according to claim 1, characterized in that: The compatibilizer is one or more of ethylene-acrylate-glycidyl methacrylate copolymer, maleic anhydride grafted polypropylene, maleic anhydride grafted polyethylene, and butylene terephthalate.
9. The environmentally friendly degradable thermal insulation fiber according to claim 1, characterized in that: The other auxiliary agents are one or more of antioxidants, light stabilizers, lubricants, and mildew inhibitors.
10. A method for preparing the environmentally friendly degradable thermal insulation fiber according to any one of claims 1 to 9, characterized in that: The steps include: T1. Mixing polylactic acid resin, bio-based thermal insulation filler, compatibilizer, modified activated carbon, silane coupling agent, and other additives to obtain a mixture; T2, heating and melting the mixture, extruding and granulating, and obtaining polylactic acid masterbatch; T3, heating and melting the polylactic acid masterbatch, spraying and spinning, and obtaining the fiber body; T4. Heat-treat the fiber body for 5-15 minutes at a temperature of 90-110°C and a draft of 3-8%, and cool it to room temperature to obtain an environmentally friendly degradable thermal insulation fiber.